STRATEGI PENGURUS PANTI ASUHAN DALAM MENANAMKAN NILAI-NILAI KEAGAMAAN DI PANTI ASUHAN ABU BAKAR SARI KOTA JAMBI - Redi Apriansyah; Salahuddin Salahuddin; Mukhlis Mukhlis (STKIP Pesisir Selatan, 2026)
This study aims to examine the strategies implemented by orphanage administrators in instilling religious values in foster children. The cultivation of religious values is an important aspect in shaping the character and personality of children Abu Bakar Sari, especially those living in orphanages. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of orphanage administrators and foster children. The results indicate that the strategies used by orphanage administrators in instilling religious values include habituation of religious activities, exemplary behavior of administrators, providing advice, as well as continuous supervision and guidance. Supporting factors in the implementation of these strategies include the commitment of administrators, a religious-oriented orphanage environment, and adequate facilities. Meanwhile, inhibiting factors include differences in the backgrounds of foster children and limited time availability of administrators. Therefore, the strategies applied by orphanage administrators play an important role in instilling religious values and shaping the religious character of foster children.